Characteristics of gut microbiota in children with language developmental delay - Yawen Li; Shouyi Wang; Huiping Xu; Xuan Nie; Dongchi Zhao; Wenkai Zhu; Rui Zhu (Frontiers in Pediatrics, 2026)
Objective To explore the characteristics of gut microbiota in children with Language Developmental Delay (LDD). Methods Children aged 0–6 years diagnosed with LDD at the Pediatric Outpatient Department of Zhongnan Hospital of Wuhan University, and healthy children undergoing physical examinations during the same period (June 2023 to June 2024) were enrolled as study subjects. Fecal samples were collected, and the characteristics of gut microbiota were assessed using 16S rDNA high-throughput sequencing. Results A total of 50 children were enrolled, including 24 in the LDD group average age (4.1 ± 1.7) years and 26 in the control group average age (4.0 ± 1.5) years, with no significant demographic differences ( P > 0.05). The Gesell developmental score in the LDD group (60 ± 12) was significantly lower than that in the control group (102 ± 15) ( P < 0.05). At the phylum level, the dominant phyla were Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria, with no significant difference in abundance between groups ( P > 0.05). Alpha diversity indices, including Observed species, Chao1 index, Shannon index, and Simpson index, showed no significant difference ( P > 0.05). Beta diversity analysis (PCoA) revealed no significant difference in microbial community structure between the two groups. Linear discriminant analysis Effect Size (LEfSe) analysis (LDA score > 2) indicated that the LDD group lacked certain bacterial taxa compared to the control group, including Mycobacteriaceae, Sphingobacteriaceae, Sphingobacteriales, Sphingobacteriia, Caulobacteriaceae, Caulobacterales, Erythrobacteraceae, Sphingomonadaceae, and Sphingomonadales. Conclusion Children with Language Developmental Delay exhibited gut microbial dysbiosis, but no specific gut microbial composition was identified.